The Construction of the Meaning of Care: Practices and Pedagogy in Nursing Education - Rojas Tapia, Tania (2025)
Nursing is a profession that integrates theoretical knowledge with human, empathetic, and experiential understanding. This study aimed to explore how the nursing faculty constructs the meaning of care within theoretical-practical modules. A descriptive methodology with a phenomenological approach was employed, involving semi-structured interviews based on the four dimensions of the ECCOE-VA instrument for assessing human care: (1) Patient Assistance and Support, (2) Teaching and Learning of Self-Care, (3) Teaching and Learning of Emotions, and (4) Humanism. The analysis of the transcripts revealed co-occurrences among these dimensions. Findings indicate that ethical and moral principles regulate and shape the faculty's conceptualization of care, which in turn influences how students internalize these meanings and apply them to human interactions aimed at improving patient health.